2016
DOI: 10.1111/1471-0307.12241
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel milk‐based fermented product fortified with wheat germ

Abstract: Wheat germ (WG) was mixed with water (1:5), heated (85°C/15 min), cooled and used to replace 0, 20, 30 and 40% (w/w) of standardised cow's milk (3% fat), supplemented with 2%(w/w) skim milk powder. Yoghurt-like fermented products were prepared from the different formulations, stored at 7 AE 2°C for 15 days, and analysed for chemical composition, pH, microbiological quality, texture profile (TPA), viscosity, syneresis and sensory properties. The addition of WG slurry enhanced acid development during fermentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…Indeed, it is well known that the pH decrease could be explained by the fact that S. thermophilus produces little amounts of formic acid and CO2 59 . The obtained results in this research agree well with those reported by Seleet et al 60 Benahmed-Djilali et al 5 , and Lukova et al 16 .…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, it is well known that the pH decrease could be explained by the fact that S. thermophilus produces little amounts of formic acid and CO2 59 . The obtained results in this research agree well with those reported by Seleet et al 60 Benahmed-Djilali et al 5 , and Lukova et al 16 .…”
Section: Discussionsupporting
confidence: 93%
“…Several reports indicated that date syrup contains appreciable amounts of phenolic compounds, having antimicrobial activity [ 46 , 58 ]. The total microbial counts in this study were comparable with those reported in traditionally produced yogurt [ 59 ], fermented milks [ 60 , 61 ], and fermented milk fortified with wheat germ [ 62 ]. The counts of yeasts and molds were affected by both the addition of date syrup and by storage conditions.…”
Section: Resultssupporting
confidence: 83%
“…In yogurt samples, the smallest number of (5.72 log cfu g -1 ) streptococci was counted in the C sample on the 1 st day of storage while the largest was detected in PC (6.92 log cfu g -1 ) on the 14 th day. It was found in Seleet et al (2016) that the number of streptococci subjected to different treatments decreased in wheat germ added probiotic yogurt in increasing storage time. Such a condition may result from inadequate lactobacilli counts in the products because streptococci grow depending on the presence of lactobacilli metabolites (Tamime & Robinson 1999).…”
Section: Microbiological Evaluationmentioning
confidence: 99%
“…However, the number of such bacteria having benefits to human health is not so clear, but estimated to be between 10 6 and 10 9 cfu g -1 (Abadía-García et al 2013). Dairy products, fermented by bacteria such as yogurt, can provide convenient media for probiotic microorganisms and have turned out to be an important sector including functional food (Cruz et al 2013;Seleet et al 2016) with the raising awareness that consumption of such products may have benefits to human health (Seleet et al 2016).…”
Section: Introductionmentioning
confidence: 99%